Digital Storybook Media Development in Pancasila Lessons in Cultivating an Attitude of Respect in Grade IV of Muhammadiyah 18 Elementary School, Medan - Balqis Fariha Nst (Berpusi Publishing, 2026)
The presence of digital technology offers various opportunities to enrich learning, including in Pancasila Education. Likewise, the rapid development of technology opens up wider opportunities for researchers to design storybooks by integrating technology into them. Digital technology can facilitate a more interactive, collaborative, and life-relevant learning process for students, so that Pancasila values are not only understood cognitively but also internalized and applied in everyday life. A digital storybook is a combination of a physical storybook and digital technology. Storybooks that initially only consisted of images and narrative text can now have audio, music, and other features. The research method used is research and development (R&D) adopting the 4D development model ( Define, Design, Development, Dissimilate ). However, in this study the researcher only reached the Dissimilate stage. The population in this study were fourth grade students of SDMuhammadiyah 18 Medan, with a total of 22 students, 8 male students and 14 female students. The main instruments in this development were the Validation Questionnaire Sheet and the Practical Questionnaire Sheet. The results of this study indicate that the Digital Storybook media on the material of Respect Attitude is declared valid and practical. The level of validity and practicality of the Digital Storybook media is seen based on the assessment by the Media Validator obtained a value of